FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KOPI INDONESIA DI PASAR JEPANG - Suhela Putri Nastuion Nasution; Abdurrozzaq Hasibuan (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2023)
The aim of the research is to determine the factors that influence Indonesian coffee exports to the Japanese market. The independent variables contained in this research are Japan's Gross Domestic Product (GDP), world coffee prices, Japanese coffee prices, exchange rates and Indonesian coffee production, while the dependent variable in this research is Indonesian coffee exports to the Japanese market. Monthly secondary data (Time Series) for the period January 2010 to December 2021. Data sources were obtained from the Central Statistics Agency (BPS), the International Coffee Organization (ICO), the Directorate General of Plantations and the World Bank. Data analysis used multiple linear regression. Simultaneous test results (F Test), the variables Gross Domestic Product (GDP), world coffee prices, Japanese coffee prices, exchange rates, and Indonesian coffee production simultaneously have a significant effect on Indonesian coffee exports to the Japanese market. The results of the partial test (t test), the variables Gross Domestic Product (GDP), world coffee prices, Japanese coffee prices and Indonesian coffee production partially have a significant effect on Indonesian coffee exports to the Japanese market. Meanwhile, the exchange rate variable partially has an insignificant effect on Indonesian coffee exports to the Japanese market.